Kesiapan Sekolah Menghadapi OSN Ekonomi SMA Di Kota Padang - Yuhendri L.V (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2018)
The development of information technology has spawned the innovation of learning technology, one of which is the application of E-learning that develops along the paradigm of learning changes. Implementation of E-learning in addition to providing benefits are also still faced with various problems that become challenges in the application of E-learning resulting in a variety of perceptions that develop in society. This article aims to describe the opportunities, challenges, and implementation of E-learning in Indonesia. This paper is a literature review by using relevant sources related to theoretical and empirical reviews of E-learning challenges, opportunities, and implementation. Sources of theoretical reviews use books, other documents on E-learning, while for empirical reviews using research results published in scientific journals.